2009
DOI: 10.1016/j.jcmg.2009.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Intravascular Thrombi With Diagnostic Ultrasound and Intravenous Microbubbles

Abstract: The purpose of this study was to determine whether high mechanical index (MI) impulses from diagnostic ultrasound (DUS) could dissolve intravascular thrombi using intravenous microbubbles. Using a canine model, DUS was applied during a continuous intravenous infusion of microbubbles. Completely thrombosed grafts were assigned to 2 treatment regimens: low-MI (<0.5-MI) ultrasound alone; or intermittent high-MI impulses (1.9-MI) guided by low-MI ultrasound (contrast pulse sequencing). A 20-MHz cavitation detector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
56
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 4 publications
1
56
0
1
Order By: Relevance
“…Multiple animal studies have demonstrated that ultrasound in combination with microbubbles can recanalize acute intravascular thrombi in large vessels, including the iliofemoral arteries, 18,19 arteriovenous grafts, 20,21 central venous catheters, 22 coronary arteries, 23 and intracranial arteries, 24,25 underlining the potential of the treatment for dissolving microvascular thrombi. However, data on the effects of ultrasound and microbubble (US+MB) treatment on the thrombolysis of microthrombi are lacking, and it is unclear whether US+MB treatment may improve the outcomes of acute ischemic stroke induced by cerebral microthrombi.…”
mentioning
confidence: 99%
“…Multiple animal studies have demonstrated that ultrasound in combination with microbubbles can recanalize acute intravascular thrombi in large vessels, including the iliofemoral arteries, 18,19 arteriovenous grafts, 20,21 central venous catheters, 22 coronary arteries, 23 and intracranial arteries, 24,25 underlining the potential of the treatment for dissolving microvascular thrombi. However, data on the effects of ultrasound and microbubble (US+MB) treatment on the thrombolysis of microthrombi are lacking, and it is unclear whether US+MB treatment may improve the outcomes of acute ischemic stroke induced by cerebral microthrombi.…”
mentioning
confidence: 99%
“…UCAs such as microbubbles have proved effective in curing intravascular thrombus [4]. Kaneko et al disclosed that high-intensity focused ultrasound associated with UCAs could be used in the liver treatment [5].…”
Section: Introductionmentioning
confidence: 99%
“…Low-frequency ultrasound and microbubble have been shown to accelerate thrombolysis in vitro and in vivo. 14,15 In addition, low frequency ultrasound has also been effective for suppressing tumour proliferation and for promoting tumour apoptosis.…”
Section: Introductionmentioning
confidence: 99%